The outcome of enhanced recovery after surgery vs. a traditional pathway in adolescent idiopathic scoliosis surgery: A retrospective comparative study - Ding, Hongtao; Hai, Yong; Guan, Li; Liu, Yuzeng; Pan, Aixing; Han, Bo (Frontiers in Surgery, 2022)
Objectives. The optimized enhanced recovery after surgery pathway for adolescent idiopathic scoliosis (AIS) patients has not been comprehensively described. The purpose of the study was to explore the feasibility and efficacy of an integral process of Enhanced Recovery after Surgery (ERAS) protocol in posterior spinal fusion (PSF) surgery for AIS patients without three-column osteotomy. Methods. Based on the inclusion and exclusion criteria, a total of 90 AIS patients underwent PSF were enrolled in the study. 45 patients followed a traditional pathway (TP) perioperative care and 45 were treated with an ERAS protocol designed and implemented by a multidisciplinary team. Patient demographic, clinical information, surgical data and radiographic parameters were collected and analyzed retrospectively. Results. There is no significant difference in age, gender, body mass index (BMI), preoperative hemoglobin level, cobb angle, curve type, average correction rate, fusion segments and screw number between ERAS group and TP group. Regarding to the estimate blood loss (EBL), surgical duration, pain intensity, drainage duration, drainage volume, first ambulation time, postoperative length of stay (LOS) and the incidence of blood transfusion, they were significantly less in ERAS group than those of TP group. Conclusions. Based on our findings, we found that the implement of a standard ERAS protocol in AIS correction surgery could result in less EBL, lower pain intensity, early ambulation, shorter LOS and rapid rehabilitation. We recommend wide-spread adoption of ERAS protocols in AIS surgery.